(untitled) (International journal of artificial intelligence, 2024)
This paper explores the methodology of integrating new pedagogical technologies to enhance the teaching of disaccharides and polysaccharides in school studies. Emphasis is placed on utilizing digital tools, interactive methods, and real-world applications to foster active learning and student engagement. Key strategies include the use of virtual simulations, augmented reality, inquiry-based learning, and flipped classrooms to simplify complex biochemical concepts. The paper also highlights the significance of laboratory experiments and collaborative tools in building a deeper understanding of carbohydrate structures and their biological importance. This approach aims to improve conceptual clarity and promote critical thinking skills among students.